Klippel-Feil syndrome in an infant - Elayne Esther Santana Hernández; Víctor Jesús Tamayo Chang; Ana María González Anta (Centro Provincial de Información de Ciencias Médicas, 2022)
The case report of an 11 months infant is presented, who was referred to the Clinical Genetics Service of the Medical Genetics Provincial Center in Holguín province, due to facial dysmorphias associated with motor retardation, short neck and decreasing movements. Interrogation, exhaustive physical exam and radiological studies of cervical column were carried out that showed the fusion of cervical vertebras, which allowed to diagnose the Klippel-Feil syndrome. A qualification with exercises was projected to strengthen the paravertebral muscles and genetic advice to the family was provided.